Improving collegiate student-athletes’ well-being: exploring the roles of openness to experience, knowledge sharing and perceived coaching effectiveness - Ni, Peihao; Feng, Ligang (Frontiers in Psychology, 2023)
Collegiate student-athletes often face various stressors from academic study and athletic training, which could harm well-being. While previous studies have highlighted the roles of university support and coaching effectiveness, scholars have neglected the personality and perception of collegiate student-athletes regarding how those supports are effective, nor was much research regarding how to obtain knowledge from peers to cope with stressors. Drawing on social learning theory, this study examines two important antecedents (collegiate student-athletes' openness to experience & knowledge sharing) of collegiate student-athlete well-being, and the moderating role of perceived coaching effectiveness. We proposed and tested a conceptual framework using an online survey (N = 484) of collegiate student-athletes from a southeastern province of China. Our results suggest that openness to experience has a positive impact on knowledge sharing (β=0.552, p<0.05), knowledge sharing with peers positively affects collegiate student-athlete well-being (β=0.415, p<0.05), and mediates the relationship between openness to experience and collegiate student-athlete well-being (β=0.086, p<0.05); perceived coaching effectiveness positively moderates the relationship between openness to experience and knowledge sharing (β=0.170, p<0.05). Our findings present theoretical contributions to collegiate student-athlete literature and managerial implications for universities and coaches.  P8: Recognize opposing team's strengths during competition.  P9: Understand competitive strategies.  P10: Adapt to different game situations.  P11: Recognize opponents' weaknesses during competition.  P12: Make critical decisions during competition.  P13: Maximize his strengths during competition.  P14: Adjust his game strategy to fit his talent. Technique  P15: Demonstrate the skills of his sport.  P16: Coach individual athletes on technique.  P17: Develop athletes' abilities.  P18: Recognize talent in athletes.  P19: Detect skill errors.  P20: Teach the skills of his sport. Character Building  P21: Instill an attitude of good moral character.  P22: Instill an attitude of fair play among his athletes.  P23: Promote good sportsmanship.  P24: Instill an attitude of respect for others.